0
$\begingroup$

Im trying to change the base log from ln to log with the following formula.

 y = a * ln⁡(x+c) + b

The ln equation is:

y = 17.686797186426052  * ln(x + 0.3) + -79.52230886298399  

And considering that:

ln(X)=2.302585 log(X) 

I was trying to change the equation to use log function (to this):

y = 17.686797186426052  * 2.302585 *  log(x + 0.3) + -79.52230886298399   

However, for some reason it's not working. Id be really grateful for some pointers on where I might be going wrong?

Cheers

$\endgroup$
1
$\begingroup$

Rewrite the formula as $$ \begin{align} y&=a\ln(x+c)+b\\ &=a\log_e(x+c)+b\\ &=a\frac{\log_k(x+c)}{\log_k e}+b\\ &=\frac{a}{\log_k e}\cdot\log_k(x+c)+b.\\ \end{align} $$ If you want the logarithm in base-$10$, then you simply write $$ y=\frac{a}{\log e}\cdot\log(x+c)+b. $$ Now, you can plug in the values of $a$, $b$, and $c$ without having trouble.

$$\\$$


$$\Large\color{blue}{\text{# }\mathbb{Q.E.D.}\text{ #}}$$

$\endgroup$
  • $\begingroup$ Hi thanks for the answer. Im wondering what "log e" means? is that log(2.71828), or log(x) * 2.71828 ? $\endgroup$ – Ke. Apr 7 '14 at 14:45
  • $\begingroup$ @Ke. $\log_e x$ means the base of logarithm is $e$, the Euler's number and $e=2.71828...$. To understand what is base in the logarithm, take a look this one: $$ \log_a x=b\;\quad\;\Rightarrow\;\quad x=a^b. $$ Similarly $$ \log_e x=b\;\quad\;\Rightarrow\;\quad x=e^b. $$ Hence, $\log_e x\neq\log(2.71828)$ or $\log_e x\neq2.71828\log(x)$. $\endgroup$ – Tunk-Fey Apr 7 '14 at 15:06
  • $\begingroup$ Many thanks for your help :) $\endgroup$ – Ke. Apr 7 '14 at 16:30
  • $\begingroup$ @Ke. You are welcome my friend. :) $\endgroup$ – Tunk-Fey Apr 7 '14 at 16:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.